2021
DOI: 10.3390/ma14206215
|View full text |Cite
|
Sign up to set email alerts
|

Space Maintainers Used in Pediatric Dentistry: An Insight of Their Biosecurity Profile by Applying In Vitro Methods

Abstract: Space maintainers have presented an increased interest due to their chemical composition which influences the electrochemical and electrolytic processes of the oral cavity, leading to important biological activity. The present study was purported to evaluate the biological in vitro activity of three types of space maintainers (S1, S2, and S3, differing from each other in terms of metal composition) used in pediatric dentistry, in terms of their antimicrobial effect and biosecurity profile using two types of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…España concuerda con que la atención odontológica se ha tenido que adaptar a esta nueva realidad frente a la pandemia recomendando la importancia de trabajar a cuatro manos con disponibilidad de infraestructura adecuada y la responsabilidad del odontólogo a estar constantemente actualizándose en el manejo de los protocolos de bioseguridad entre ellos el manejo de los aerosoles con énfasis a la ventilación de los ambientes como el manejo de la buena calidad de aire en los ambientes (Luca et al, 2021).…”
Section: Discussionunclassified
“…España concuerda con que la atención odontológica se ha tenido que adaptar a esta nueva realidad frente a la pandemia recomendando la importancia de trabajar a cuatro manos con disponibilidad de infraestructura adecuada y la responsabilidad del odontólogo a estar constantemente actualizándose en el manejo de los protocolos de bioseguridad entre ellos el manejo de los aerosoles con énfasis a la ventilación de los ambientes como el manejo de la buena calidad de aire en los ambientes (Luca et al, 2021).…”
Section: Discussionunclassified
“…Based on chemical reactions or plasma-promoted chemical reactions, it has been widely used in the manufacturing methods of microelectronics and protective coatings of cermets. 29 Fix et al reported that crystalline TiN and Zr 3 N 4 films were prepared by CVD technology with metal and diethylamino complexes under atmospheric pressure. 30 Wang et al used WO 3 and NaCl mixed powders as precursors and reacted with ammonia at a certain temperature to obtain WN crystals deposited on the substrate (Fig.…”
Section: The Main Synthesis Methods Of Transition Metal Nitridesmentioning
confidence: 99%
“…Afterward, the cells were exposed to SLN samples; also, control cells were included, which were treated only with a culture medium. Quantification of the cell viability rate was determined by reading the absorbance at two different wavelengths (570 nm and 600 nm) using the xMark TM microplate reader (Bio-Rad Laboratories, Hercules, CA, USA) and applying a previously published formula [57].…”
Section: Cell Viability Evaluationmentioning
confidence: 99%